2015
DOI: 10.1016/j.jphys.2014.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Walking training with cueing of cadence improves walking speed and stride length after stroke more than walking training alone: a systematic review

Abstract: PROSPERO (CRD42013005873).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 25 publications
10
77
0
Order By: Relevance
“…To date, three strategies have been explored to encourage individuals to walk at moderate intensity with a walking cadence prescription, mostly in a cross-sectional manner: first, through the utilization of auditory cues, using metronomes or music for pacing in apparently healthy adults [3235] and clinical populations [36, 37]; second, by asking participants to self-perceive intensity [32, 38, 39]; third, by providing a pedometer with a target cadence to follow [4042]. As of now, few pedometers, displaying walking cadence at different intensities, have been validated [34, 46].…”
Section: Resultsmentioning
confidence: 99%
“…To date, three strategies have been explored to encourage individuals to walk at moderate intensity with a walking cadence prescription, mostly in a cross-sectional manner: first, through the utilization of auditory cues, using metronomes or music for pacing in apparently healthy adults [3235] and clinical populations [36, 37]; second, by asking participants to self-perceive intensity [32, 38, 39]; third, by providing a pedometer with a target cadence to follow [4042]. As of now, few pedometers, displaying walking cadence at different intensities, have been validated [34, 46].…”
Section: Resultsmentioning
confidence: 99%
“…Several of the systematic reviews and meta-analyses have also suggested a similar temporal course for auditory-motor training regimens to allow enhancements in motor performance. [29][30][31][32][33][34] In the present research, we aim to address the limitations of the experimental design used, and also to elucidate the influence of auditory feedback on motor learning. An expanded intermodal auditoryproprioceptive training protocol has been developed to investigate the efficacy of real-time auditory information on proprioceptive motor learning.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 90% of stroke survivors have residual disabilities, such as muscle weakness on one side of the body and sensory disturbances that lead to limited performance in walking [3][4][5] and impaired upper extremity (UE) function 4,7 . This results in problems with activities of daily living (ADL) [8][9][10] and community participation 11 .…”
Section: Introductionmentioning
confidence: 99%